Emergent trophic interactions following the Chinook salmon invasion of Patagonia. Issue 2 (3rd February 2022) - Muñoz, Nicolas J.; Reid, Brian; Correa, Cristian; Madriz, Ruben Isaí; Neff, Bryan D.; Reynolds, John D.
Abstract: In their native range, Pacific salmon ( Oncorhynchus spp.) have strong interactions with a multitude of species due to the annual pulse of marine‐derived nutrients that they deliver to streams and forests when they spawn and die. Over the past few decades, Chinook salmon ( Oncorhynchus tshawytscha ) has established non‐native populations throughout the Patagonia region of southern South America. Here, we provide the first assessment of the pathways through which salmon‐derived nutrients enter stream and forest food webs in Patagonia by surveying multiple streams in southern Chile to identify invertebrate and vertebrate consumers of salmon carcasses and summarizing all documented trophic interactions of Chinook salmon in Patagonia. Blowflies (Calliphoridae) were the dominant colonizer of carcasses in the riparian zone, and midge flies (Chironomidae) were the most common invertebrate on submerged carcasses. Camera trap monitoring in the riparian zone revealed consumption of carcasses or carcass‐associated invertebrates by the insectivorous passerine bird "chucao" ( Scelorchilis rubecula ), small rodents (black rat Rattus rattus, house mouse Mus musculus, and/or colilargo Oligoryzomys longicaudatus ), the South American fox "culpeo" ( Lycalopex culpaeus ), and the invasive American mink ( Neovison vison ). A mink was filmed transferring a carcass from stream to streambank, indicating that vertebrate scavenging likely increases the degree to which marine‐derived nutrients enter terrestrial food webs. The native taxa that consume salmon are closely related to species that benefit from salmon consumption in North America, suggesting that the pathways of salmon nutrient incorporation in North American food webs have functionally re‐emerged in South America. Similarly, non‐native trout ( Oncorhynchus mykiss and Salmo trutta ) and mink consume salmon in Patagonia, and their eco‐evolutionary history of coexistence with salmon could mean that they are preadapted for salmon consumption and could thus be key beneficiaries of this invasion. Expanded monitoring of the abundance and impacts of salmon will be vital for understanding how these novel inputs of marine‐derived nutrients alter Patagonian food webs.